The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1097/hmr.0000000000000138
|View full text |Cite
|
Sign up to set email alerts
|

Fostering evidence-based quality improvement for patient-centered medical homes: Initiating local quality councils to transform primary care

Abstract: In order to successfully facilitate systematic, sustainable primary care quality improvement, regional and executive health care system leaders should engage interdisciplinary practice level leadership in a priority-setting process that encourages frontline innovation and establish local structures such as quality councils to coordinate quality improvement initiatives, ensure accountability, and promote spread of best practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…The informal caregivers reported that the hospital services were concerned with examining the patients, diagnosing them and returning them back home as rapidly as possible. Despite decades of attention to the principles of activating, empowering and engaging the patients in their own healthcare [9,[53][54][55] as part of securing patientcenteredness as a cornerstone of healthcare service quality [54,56], the informal caregivers reported a health service that did not appear to be responsive to the patients' or the informal caregivers' preferences or needs. Instead, the informal caregivers we interviewed found the health services in the municipality to be focused on short visits from healthcare personnel and the delivery of health services rather than helping with practical tasks.…”
Section: Discussionmentioning
confidence: 99%
“…The informal caregivers reported that the hospital services were concerned with examining the patients, diagnosing them and returning them back home as rapidly as possible. Despite decades of attention to the principles of activating, empowering and engaging the patients in their own healthcare [9,[53][54][55] as part of securing patientcenteredness as a cornerstone of healthcare service quality [54,56], the informal caregivers reported a health service that did not appear to be responsive to the patients' or the informal caregivers' preferences or needs. Instead, the informal caregivers we interviewed found the health services in the municipality to be focused on short visits from healthcare personnel and the delivery of health services rather than helping with practical tasks.…”
Section: Discussionmentioning
confidence: 99%
“…The informal caregivers reported that the hospital services were concerned with examining the patients, diagnosing them and returning them back home as rapidly as possible. Despite decades of attention to the principles of activating, empowering and engaging the patients in their own healthcare [9,[53][54][55] as part of securing patient-centeredness as a cornerstone of healthcare service quality [54,56], the informal caregivers reported a health service that did not appear to be responsive to the patients' or the informal caregivers' preferences or needs. Instead, the informal caregivers we interviewed found the health services in the municipality to be focused on short visits from healthcare personnel and the delivery of health services rather than helping with practical tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Some of our participants even reported that they were not asked or allowed to have an opinion about their own healthcare. Despite decades of attention to principles of activating, empowering and engaging the patients in their own healthcare [9,[47][48][49] as part of securing patient centeredness as a cornerstone of healthcare service quality [48,50], the service did not appear to be responsive to older patients' preferences or needs.…”
Section: Discussionmentioning
confidence: 99%